Understanding history in Asia : what diplomatic documents reveal - Hattori, Ryūji, 1968-; Cannon, Tara (Tokyo, Japan : Japan Publishing Industry Foundation for Culture, 2019)
The twentieth century has been called a century of war. Wars and colonization leave deep chasms between countries. In the case of Japan, these frictions have manifested themselves as historical issues. The history since World War II has also been a history of trying to overcome the hostility surrounding these issues. Since the end of the war there have been various attempts at reconciliation, and indeed, periods in which Japan has enjoyed good relations with China and also with South Korea. Despite that, historical issues have overheated in the twenty-first century, and their effects may extend beyond Japan's relations with China and South Korea to impact its relations with the United States, Southeast Asia, and Europe. --
The Japanese history textbook issue and "mutual trust". -- Official visits to Yasukuni shrine. -- The comfort women issue. -- The Murayama statement. -- Going beyond the century of war.
Donación de la Embajada de Japón.
Título original: Gaikō dokyumento rekishi ninshiki.
datos biográficos del autor en la página [268]
Bibliografía: páginas 237-263.
Keywords: RELACIONES INTERNACIONALES; DIPLOMACIA; DOCUMENTOS DIPLOMATICOS -- ASIA; JAPON -- RELACIONES EXTERIORES -- CHINA; CHINA -- RELACIONES EXTERIORES -- JAPON; COREA DEL SUR -- RELACIONES EXTERIORES -- JAPON; JAPON -- RELACIONES EXTERIORES -- COREA DEL SUR